Neurodevelopmental profile and poverty in primary school confer a ‘double disadvantage’ in risk of criminal justice system contact by the age of 16: A national prospective cohort study. - Kent, Hope; Hogarth, Lee; Williams, Huw; Cornish, Rosie; Leckie, George (International Journal of Population Data Science, 2025)
Objectives Children with neurodisabilities (such as brain injury or autism), and children who live in poverty, are over-represented groups in the youth justice system. This study examined the intersectional disadvantage faced by children who have both of these risk factors, to inform preventative public health strategies for reducing child criminalisation. Methods We used linked Ministry of Justice and Department for Education data, relating to a birth cohort of children born in 2001/2002, who attended state (government funded) school in England (n = 519,920). We used means-tested Free School Meals eligibility in Reception year (the first year of formal schooling, aged 4/5) to index child poverty, and the Early Years Foundation Stage Profile (EYFSP) (aged 4/5) to index early functional development across six domains. Our outcome variable was having a caution or conviction before age 15/16. We controlled for gender, ethnicity, and birth month. Results 1.3% of children had a caution or conviction before the age of 15/16. Higher z-scores on the EYFSP (indicating better functional development) were associated with decreased odds of a caution or conviction by the age of 15/16 (adjusted OR for 1SD increase in z-score = 0.70, 95% CI = 0.69–0.72). Being eligible for Free School Meals (living in absolute poverty) at age 4/5 was associated with increased odds of having a caution or conviction by age 15/16 (adjusted OR = 4.62, 95% CI = 4.46–4.92). There was a statistical interaction between these two risk factors (adjusted OR = 1.33, 95% CI = 1.27–1.39). Children living in poverty had consistently higher risk at every z-score on the EYFSP, and living in poverty worsened the absolute risk conferred by lower z-scores on the EYFSP. Conclusion Poverty and lower functional development independently confer risk of criminalisation, and together confer a ‘double disadvantage’. Structural public health interventions should reduce the criminalisation of children by improving Special Educational Needs support in schools, and by reducing the number of children living in absolute poverty.